Using software tools : WordStar 4.0, VP-planner/Lotus, and dBase III plus - Saret, Laura; Dublin, Peter (New York : McGraw Hill Education, 1988)
This book will help you learn some of the programs used by businesses as tools to increase productivity, manage data, and aid in decision making.
Module I. Getting started -- Module II. Wordstar -- Module III. VP-Planner/Lotus -- Module IV. dBase III plus.
Includes bibliographical references and index.
Keywords: COMPUTER PROGRAMMING LANGUAGE